PENGARUH CITRA MEREK, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN BEKAS PADA APLIKASI OLX JAKARTA - Raihan Setyoaji Alamsyah, (2022)
This research is a quantitative research that aims to determine the effect of brand image, service quality, and promotion on purchasing decisions. This research took the population of used vehicle buyers through the OLX application in the DKI Jakarta area. The sample size is 100+30 respondents. The sampling method is non-probability sampling and the samples are taken using purposive sampling technique. This study uses data from the results of dissemination through questionnaires. Data analysis in this study is the Multiple Linear Regression analysis method using SPSS Software Version 29. The results of the study show that brand image and service quality have a positive and significant impact on purchasing decisions. Then, Promotion has no influence on Purchasing Decisions. While Brand Image, Service Quality, and Promotion simultaneously have an influence on purchasing decisions.